Analysis of a power generation project in the face of increased demand for Liquefied natural gas (LNG) in the context of the new gas market (Research, Society and Development, 2022)
Natural gas is the primary fuel for Brazil's current expansion of thermoelectric generation. Imported LNG is considered a relevant energy source for developing new energy sources intermittently in the short and medium-term through plants that operate in the GW (gas-to-wire) and RTW (reservoir-to-wire) model. Given potentialities and restrictions, this study aimed to evaluate the prospects of using LNG as an alternative energy source. This article will use bibliographic, analytical, and qualitative methods and the SWOT tool. With this in mind, the expected results for analyzing strengths, opportunities, weaknesses, and changes in the expansion of LNG consumption refer to Eneva's Azulão Jaguatirica project. This research contributes to the debate on construction decision-making, the beginning of the operation of LNG terminals with a focus on thermoelectric generation, using the objective of the SWOT matrix